1989
DOI: 10.1210/endo-124-3-1365
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Lithium on the Release of Thyroid Hormones from Thyrotropin-Stimulated Mouse Thyroids in a Perifusion System*

Abstract: We studied the effect of lithium on the release of T3, T4, and cAMP from perifused mouse thyroids and on cAMP content in thyroid pieces. Lithium significantly inhibited T3 and T4 release from TSH-stimulated mouse thyroids. This inhibitory effect on thyroid hormone release was dependent on the concentration of lithium. Under continuous stimulation with TSH and 3-isobutyl-1-methylxanthine, both cAMP release and cAMP content were significantly decreased by lithium. In addition, we studied the effect of lithium on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 14 publications
0
17
1
Order By: Relevance
“…[8][9][10] Lithium increases retention of 131 I in the thyroid. 8,11 Furthermore, because of its inhibitory effects on thyroid hormone release, 11,12 lithium may attenuate the initial rise in circulating thyroid hormones that occurs following RAI administration. [13][14][15] However, to date, it has not been clearly demonstrated that adjuvant lithium actually improves RAI efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Lithium increases retention of 131 I in the thyroid. 8,11 Furthermore, because of its inhibitory effects on thyroid hormone release, 11,12 lithium may attenuate the initial rise in circulating thyroid hormones that occurs following RAI administration. [13][14][15] However, to date, it has not been clearly demonstrated that adjuvant lithium actually improves RAI efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Lazarus et al 1981). Lithium has been found to inhibit TSH-stimulated thyroid hormone release from thyroid tissue in vitro (Williams et al 1971, Mori et al 1989. Lithium-induced resistance to TSH can be demonstrated in pig thyroid cells where 1 mM inhibits TSH-stimulated cAMP accumulation within 30 min (Wragg & Mac Neil 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Valle et al (10) have also reported hypothyroidism from biochemical, haematologic, histometric and ultrastructural changes of the thyroid gland after lithium treatment in adult rats. Serum T 3 and T 4 levels are declined in rats (31,32) and in patients with unipolar depression (33). A significant decrease in FT 4 and FT 3 has also been reported after lithium treatment in male rats.…”
Section: Discussionmentioning
confidence: 99%